The Impact of Consumer Knowledge in Making Decisions to Purchase Tupperware Environmentally Friendly Products in Makassar City - Syukur, Muhammad; Seppa, Yusi Irensi; Arifin, Ibrahim (Universitas Negeri Makassar, 2023)
Study This aim For know impact from knowledge consumer in taking decision purchase product friendly Tupperware environment in Makassar City. Type research used is study qualitative descriptive that can help researcher with explain the realities on the ground. Data collection techniques in the form of Observation , Interview and Documentation . Data analysis techniques in the form of stage First data reduction process that focuses on selecting , simplifying , abstracting and transforming raw data from notes field . Stage second is presentation of data, ie drafting information become possible statement withdrawal conclusions , and the third stage is drawing conclusions based on data reduction and presentation. Research results show that knowledge consumer give impact positive in taking decision purchase product friendly Tupperware environment in Makassar City. it can seen from knowledge product , knowledge purchasing and knowledge usage which is part from knowledge consumers who have partially owned big informants/ consumers . With own knowledge consumers , understanding , and confidence consumer about marketed Tupperware products , then will affect behavior consumer in buy so that consumer will take decision related purchase product with buy desired Tupperware product . . Keywords : Knowledge , Consumers , Purchasing Decisions